3, 3-Diindolylmethane (DIM): a nutritional intervention and its impact on breast density in healthy BRCA carriers. A prospective clinical trial. (27th May 2020) - Yerushalmi, Rinat; Bargil, Sharon; Ber, Yaara; Ozlavo, Rachel; Sivan, Tuval; Rapson, Yael; Pomerantz, Adi; Tsoref, Daliah; Sharon, Eran; Caspi, Opher; Grubsrein, Ahuvah; Margel, David
Abstract: Women who carry the BRCA mutation are at high lifetime risk of breast cancer, but there is no consensus regarding an effective and safe chemoprevention strategy. A large body of evidence suggests that 3, 3-diindolylmethane (DIM), a dimer of indole-3-carbinol found in cruciferous vegetables, can potentially prevent carcinogenesis and tumor development. The primary aim of this prospective single-arm study was to investigate the effect of DIM supplementation on breast density, a recognized predictive factor of breast cancer risk. Participants were 23 healthy female BRCA carriers (median age 47 years; 78% postmenopausal) who were treated with oral DIM 100 mg × 1/day for 1 year. The amount of fibroglandular tissue (FGT) and background parenchymal enhancement (BPE) on magnetic resonance imaging (MRI) performed before and after the intervention was scored by two independent expert radiologists using the Breast Imaging and Reporting Data System. The results showed a decrease in the average score for FGT amount from 2.8 ± 0.8 at the onset to 2.65 ± 0.84 after 1 year ( P = 0.031), with no significant change in BPE ( P = 0.429). A group of DIM-untreated age- and menopausal-status-matched women from the BRCA clinic did not show a significant change in FGT amount ( P = 0.33) or BPE ( P = 0.814) in a parallel year. Mean estradiol level decreased from 159 to 102 pmol/l ( P = 0.01), and mean testosterone level decreased from 0.42 to 0.31 pmol/l ( P = 0.007). Side effects were grade 1. In conclusion, 1 year's supplementation with DIM 100 mg × 1/day in BRCA carriers was associated with a significant decline in FGT amount on MRI. Larger randomized studies are warranted to corroborate these findings. Abstract : The impact of 1 year's supplementation with oral 3, 3-diindolylmethane 100 mg × 1/day on breast density and estrogen metabolism was evaluated in 23 healthy BRCA carriers. MRI showed a significant decrease in average Breast Imaging and Reporting Data System score for fibroglandular tissue from before to after treatment.